PEMECAHAN MASALAH TIME VALUE OF MONEY SEBAGAI TOOLS PENILAIAN KELAYAKAN INVESTASI DENGAN MENGGUNAKAN GOOGLE-SHEET - Mardiyati Mardiyati; Hijrah Wahyudi (STIE 'INDONESIA' Pontianak, 2023)
The purpose of this research is to provide the practice of calculating future value and present value using the time value of money method through the google sheet application with the type of experimental research one shot study. The future value approach and the present value approach have significant implications for accounting records and reporting regarding the fair value of money. The results of calculations using google sheets offer solutions in terms of accuracy and speed of calculations compared to manual calculations as support for assessing the feasibility (feasible or not) of an investment.